Mammalian Orthoreovirus (MRV) Is Widespread in Wild Ungulates of Northern Italy - Sara Arnaboldi; Francesco Righi; Virginia Filipello; Tiziana Trogu; Davide Lelli; Alessandro Bianchi; Silvia Bonardi; Enrico Pavoni; Barbara Bertasi; Antonio Lavazza (Viruses, 2021)
Mammalian orthoreoviruses (MRVs) are emerging infectious agents that may affect wild animals. MRVs are usually associated with asymptomatic or mild respiratory and enteric infections. However, severe clinical manifestations have been occasionally reported in human and animal hosts. An insight into their circulation is essential to minimize the risk of diffusion to farmed animals and possibly to humans. The aim of this study was to investigate the presence of likely zoonotic MRVs in wild ungulates. Liver samples were collected from wild boar, red deer, roe deer, and chamois. Samples originated from two areas (Sondrio and Parma provinces) in Northern Italy with different environmental characteristics. MRV detection was carried out by PCR; confirmation by sequencing and typing for MRV type 3, which has been frequently associated with disease in pigs, were carried out for positive samples. MRV prevalence was as high as 45.3% in wild boars and 40.6% in red deer in the Sondrio area, with lower prevalence in the Parma area (15.4% in wild boars). Our findings shed light on MRV occurrence and distribution in some wild species and posed the issue of their possible role as reservoir.